THE ROLE OF TEACHER TRAINING IN PROMOTING INCLUSIVE EDUCATION PRACTICES IN PAKISTANI SCHOOLS - Dr. Samina Safdar; Dr. Yasira Waqar; Dr. Faisal Anis; Dr. Yaar Muhammad (International Journal of Contemporary Issues in Social Sciences, 2024)
With regard to this background, the present paper aims to explore the factors that hinder the implementation of the included education emphasis, specifically, the importance of teacher training in the improvement of teaching practices in Pakistani schools. However, the following hurdles have remained prevalent in regard to the promotion of inclusion of special education needs: Teachers are not well equipped, there are few resources to meet the needs of these children, and society does not embrace disability. This paper looks at how teacher training programs can overcome these challenges and prepare teachers for teaching diversity differences. The paper reviews today’s teacher training schemes in Pakistan and assesses their strengths, weaknesses, and prospects for development. It states that while developing the training of teachers, it is critical to consider not only the knowledge of the principles and organization of inclusive education approaches but also knowledge of how to deliver special sensitivity to the inclusiveness of learners along with strategies for instructing students with disabilities in the context of students, classrooms, and families of origin and support professionals. In addition, the paper recommends that teacher training faculties should include cultural competence and raise awareness of disability discrimination in society. It is, therefore, concluded that given schools in Pakistan invest in targeted training of their teachers, a progressive shift to pedagogy accommodative of the disabled is realistically possible, providing equal chances to every child at schools.